Could setmelanotide be the game-changer for acquired hypothalamic obesity? - van Santen, Hanneke M.; Denzer, Christian; Müller, Hermann Lothar (Frontiers in Endocrinology, 2024)
Children with acquired hypothalamic obesity, e.g. following treatment for pediatric craniopharyngioma are at great risk for metabolic syndrome, cardiovascular health problems and premature mortality. Treatment for acquired hypothalamic obesity has thus far been disappointing. Several interventions were reported to be partially successful, including dextro-amphetamine and GLP-1R agonists, although results in acquired hypothalamic obesity are conflicting. Disruption of signaling through the melanocortin-4 receptor (MC4R) pathway results in hyperphagia and severe early-onset hypothalamic obesity. Recently, the MC4R agonist setmelanotide has shown promising results in children with genetic forms of hypothalamic obesity; POMC, PCSK1 and LEPR. Patient quotes such as "we have our family life back" illustrate the magnitude of the effect. Targeted hormone replacement therapy with an MC4R agonist for acquired hypothalamic obesity could be a game-changer. Preliminary results of setmelanotide treatment in 14, mostly pediatric, patients with acquired hypothalamic obesity are promising. The FDA has recommended that a prospective, randomized, blinded trial be conducted over a 12 months treatment period, comparable to pivotal trials for other obesity drugs. It may be discussed whether setmelanotide should be regarded as an obesity drug or whether it may be envisioned as an agent for hypothalamic substitution therapy. In this commentary we discuss the trial that is currently recruiting patients with acquired hypothalamic obesity.